PRIORITIZATION METHODS AND ERROR ANALYSIS IN ANALYTIC HIERARCHY PROCESS – AN ILLUSTRATION - Shyamprasad, V.; P.Kousalya, Dr. (IJRDO -JOURNAL OF MATHEMATICS, 2016)
This paper explains about Analytic Hierarchy Process which deals selection of set of alternatives towards an overall goal. In this generally Prioritization methods are used to find the priority vector weights, three prioritization methods are used to find the priorities of Pair wise Comparison Matrix and different errors are calculated and compared. The three methods are namely (i). Least Square Error Method (LSE) (ii). Logarithmic Least Square Error Method (LLSE) and (iii). Chi-Square Error (CSE) is used to find error to the final Priority Vector and an error analysis was made.